The reasonable robot Artificial Intelligence and the law - Abbott, Ryan (United Kingdom Cambridge University Press, 2020)
"The concept of AI has ancient origins. Around the 8th Century BCE, the Greek poet Homer wrote in the Iliad about Hephaestus, the God of fire and a skilled inventor. He built golden automata, or self-operating machines, to help him work. Not only did Hephaestus build attendants for himself with "intelligence in their hearts" and the "appearance [of] living young women", he also built autonomous vehicles that could travel to and from the home of the gods, and a lethal autonomous weapon system named Talos that patrolled the beaches of Crete"--
Introduction: Artificial intelligence and the Law-- Understanding Artificial Intelligence-- Should Artificial Intelligence Pay Taxes?-- The Reasonable Robot-- The Artificial Inventors-- Everything is obvious-- Punishing Artificial Intelligence-- Alternative Perspectives on Artificial Intelligence and AI Legal Neutrality.
Includes index.
Keywords: Artificial intelligence -- Law and legislation; Personality (Law); Computers -- Law and legislation .; Internet -- Law and legislation